The Effects of Storytelling Technique on Students’ Speaking Achievement - Hartono (SELL Journal : Scope of English Language Teaching, Linguistics, and Literature, 2018)
This study aims at finding out the effects of storytelling technique on the students’ speaking achievement. This study is an experimental research. The population are 310 ninth grade students of Junior High School Kamal Bangkalan. The samples are taken with randomized sample selection technique both experimental and controlled group. The samples were taken with ordinal pairing technique, the first group was 35 students, who were given storytelling technique, and the second one was another 35 students, who were given role-play technique. The design is pretest-posttest with independent t-test as the measurement. The try out was done to another class to find out the validity and reliability of the test. The treatment was administered in eight meetings to both storytelling and role-play techniques. The writer used storytelling and role-play techniques as teaching strategies. The steps of the treatment began with pre-activities, whilst activities, post activities, and ended with feedback, reflection and closing. The finding of this study related that storytelling technique can be considered as an alternative technique in teaching speaking. The technique could improve the students’ achievement on speaking significantly. It was shown in the speaking score increase before and after the treatments.